Problems and Implementation of Government Regulation Number 1 of 2011 Regarding the Transfer of Function of Agricultural Land to Industrial Land - Abdul Kodir; Amin Purnawan; Akhmad Khisni (Sultan Agung Notary Law Review, 2021)
The threat to disruption of food security due to rampant conversion of agricultural land is very significantagainst land use change according to Government Regulation No. 1 of 2011 concerning the Designation and Transfer of Function of Sustainable Food Agricultural Land in article 35 has regulated limitatively that land that has been designated as Sustainable Food Agricultural Land is protected and prohibited from being converted. The purpose of this study is to determine the implementation of land use change according to Government Regulation No. 1 of 2011 and to find out the legal consequences of the conversion of agricultural land into industrial areas. The method used in this research is sociological juridical method, the specification in this research is descriptive analysis, data used are primary data and secondary data, using data collection by interview and literature study, qualitative data analysis, problems analyzed by theory, legal certainty, and Justice Theory. The results of this study indicate that transfer of function in Government Regulation No. 1 of 2011 concerning the Designation and Transfer of Function of Sustainable Food Agricultural Land in article 35 regulates that land that has been designated as Sustainable Food Agricultural Land is protected and prohibited from being converted. The local government can carry out the conversion of land functions in the context of land acquisition for the public interest or a disaster occurs. Industry is not included in the public interest, which is allowed to use paddy fields for conversion. Regarding law enforcement on the conversion of agricultural land functions, the central and regional governments still consider that development is merely encouraging the improvement of physical infrastructure, which often sacrifices productive agricultural land. The conversion of agricultural land to residential areas, the development of public infrastructure and industrial facilities is quite alarming so that it will have an impact on the national and regional food crisis if not handled seriously. In the midst of the food self-sufficiency target, there needs to be serious steps in law enforcement and maximum protection of productive agricultural land.